STUDY OF SOME BIOCHEMICAL CHANGES IN URINE AND SERUM OF EXPERIMENTALLY- INDUCED UROLITHIASIS RABBITS BY SODIUM OXALATE - Arwa; H.M.AL-Saeed (Basrah Journal of Veterinary Research)
The present study was undertaken to find the alteration in some urine and serum parameters of urolithiasis rabbits induced by sodium oxalate .Animals were divided into two groups six in each, first group animals received only normal saline (0.9%) as control group , while second group animals were treated with sodium oxalate (70 mg / Kg b.w intraperitoneal ) daily for 15 days as treatment group . The results of urine analysis indicated that increased urine specific gravity , protein level and leukocytes , while decreased pH in treatment group as compared with control group , also observed that hemolysis in urine but there was no significant difference (p> 0.05) in urine level of glucose , Ketones , nitrite , urobilinogen and bilirubin in treatment group as compared with control group . The results of serum analysis indicated that there was no significant difference (p> 0.05) in serum level of calcium and phosphorus , while , increased serum level of sodium , potassium , uric acid and creatinine in treatment group as compared with control group . The study indicated that there was some changes in both urine and serum parameters in urolithasis .